Design, Development, and In Vitro AGS Cell Survival of Rebamipide-Loaded Solid Lipid Nanoparticles for Gastric Cytoprotection in Peptic Ulcer Management - Rohit, Rohit; Mittal, Anuj (Journal of Neonatal Surgery, 2025)
Peptic ulcer disease (PUD), characterized by mucosal erosion in the stomach or duodenum, remains a significant global health concern. Rebamipide, a gastroprotective drug with anti-inflammatory and cytoprotective effects, suffers from poor water solubility and limited bioavailability, hindering its therapeutic efficacy. This study aimed to design and develop Rebamipide-loaded solid lipid nanoparticles (SLNs) to enhance gastric cytoprotection and investigate their performance using AGS human gastric epithelial cells in vitro. SLNs were prepared using the high-speed homogenization and ultrasonication method, with stearic acid as lipid and poloxamer 188 as a surfactant. The optimized formulation (F3) was characterized by particle size (~112 nm), polydispersity index (PDI = 0.204), zeta potential (−23.4 mV), and entrapment efficiency (~87.3%). Transmission electron microscopy confirmed spherical morphology and uniform distribution. In vitro drug release studies demonstrated a sustained release of Rebamipide over 24 hours, with initial burst release followed by controlled diffusion. Stability studies at 25°C and 40°C for three months revealed minimal change in physicochemical properties. Cytotoxicity and cell survival studies using AGS cells showed enhanced viability and proliferation in cells treated with Rebamipide-SLNs compared to the drug suspension. The nanoformulated Rebamipide significantly promoted mucosal healing and provided a protective effect against ethanol-induced damage in vitro. The study highlights the potential of SLNs as a delivery system for poorly soluble drugs like Rebamipide and opens avenues for their application in pediatric and neonatal gastroprotection, especially in critical care scenarios. Further in vivo and clinical studies are warranted to confirm translational benefits.